A comprehensive review on elimination of thiophenic compounds from crude oils through combined extractive and adsorptive desulfurization using porous liquids - Mohsen Shayanmehr; Ahad Ghaemi; Alireza Hemmati (Chemical Engineering Journal Advances, 2025)
Porous liquids (PLs) are a new class of hybrid materials that combine the permanent porosity of solids and the fluidity of liquids. Their distinctive dual functionality, facilitating both molecular adsorption and solvent-mediated extraction, renders them ideal candidates for the desulfurization of liquid fuels, particularly for the removal of thiophenic compounds. This review takes a critical assessment of PLs as combined extractive and adsorptive systems, specifically highlighting their application towards sulfur removal. A detailed analysis is given on their desulfurization performance, operational conditions, and removal mechanisms. Quantitative results show that MIL-101(Fe) functionalized with peroxo-polyoxometalates resulted in 100 %, 99.8 %, and 98.5 % removal of dibenzothiophene (DBT), 4-methyldibenzothiophene (4-MDBT), and 4,6-dimethyldibenzothiophene (4,6-DMDBT) (500 ppm) at 70 °C in 30 min. MIL-125(Ti) coupled with [Hnmp]HSO₄ IL exhibited 99.18 % DBT removal (1000 ppm) at 50 °C in a short duration of 10 min, whereas other systems like SBA-15/IL performed <60 % under more severe conditions. Apart from performance, this review discusses economic and environmental aspects, including solvent regeneration, energy efficiency, and system recyclability. Several PLs exhibit low volatility, thermal stability, and ease of recycling, resulting in minimal operational costs and a negligible environmental footprint. All in all, this work provides a critical and timely overview of PL-based solutions for next-generation desulfurization, offering strong prospects for scalable and sustainable fuel processing.